Askeri birliklerde ulaştırma modellerinin kullanılması (Kumanya dağıtım sisteminin optimizasyonu) - Ateş, Abdullah (My University, 2002)
The subject of this thesis is “the effects of the new administrative techniques on small to medium sized businesses”. In this thesis, first we will consider KOBİ’s and their problems, and then we will examine conventional administrative techniques. Next, we will examine the new administrative techniques and consequently, we will investigate their effects on KOBİ’s, rate of success and applicability. The work consists of three parts. In the first part, small and medium sized businesses are examined. In the second part, the new administrative techniques and how these can be applied to KOBİ’s are investigated. And in the third part, the effects of the news techniques and approaches on KOBİ’s are explained. Günmat Tanıtım ve Danışmanlık Ltd. Şti. has been chosen as the case study. It has been observed that, the new techniques have evolved by emphasizing and enhancing on the strong aspects of traditional administrative techniques and eliminating their weaknesses, thus becoming globally applicable. It has been decided that, the new administrative techniques can be applied to KOBİ’s. Key words: KOBİ, Administrative Techniques, New Administrative Techniques

Using Transport Models in military troops, emphasize using Operations Research techniques (especially TRANSPORT PROBLEMS ) help leaders on both battlefield and peace times. This project brings a military approach to the linear programming especially TRANSPORT PROBLEMS. On this project ; we are trying to find a solution to optimize the system of disturbution of food. There is an old way of distirbution but we are looking for a new way; new model because we try to minimize the cost and maximize the effectiveness of the disturbition. All the platoon and company commanders can use the techniques of the Operations Research. This survives optimization of cost and time. It is also easier than the other known techniques. Especially transport model is simple and easy to Simplex Method. Trasport Model will be the important factor for commanders especially on decision making process.
Keywords: Askeri Birlikler; Askeri donanım; Askerlik bilimi; Ulaştırma